2010
DOI: 10.1111/j.1460-9568.2010.07135.x
|View full text |Cite
|
Sign up to set email alerts
|

Glycine transport accounts for the differential role of glycine vs. d‐serine at NMDA receptor coagonist sites in the salamander retina

Abstract: In this study, we demonstrate that D-serine interacts with N-methyl-D-aspartate receptor (NMDAR) coagonist sites of retinal ganglion cells of the tiger salamander retina by showing that exogenous D-serine overcomes the competitive antagonism of 7-chlorokynurenic acid for this site. Additionally, we show that exogenous D-serine was more than 30 times as effective at potentiating NMDAR currents compared with glycine. We thus examined the importance of glycine transport through the application of selective antago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 49 publications
2
13
0
1
Order By: Relevance
“…Blocking NMDARs (Krystal et al, 2002) or genetically reducing NMDAR function in interneurons causes schizophrenia-like symptoms (Belforte et al, 2010). Interestingly, D-serine was found to improve positive, negative, and cognitive symptoms in patients with schizophrenia (Tsai et al, 1998(Tsai et al, , 1999. Collectively, this suggests that augmenting NMDA-mediated transmission through the NMDA coagonist binding site is promising for the pharmacotherapy of schizophrenia but perhaps also of epilepsy.…”
Section: D-serine and Novel Therapies In Epilepsymentioning
confidence: 98%
See 1 more Smart Citation
“…Blocking NMDARs (Krystal et al, 2002) or genetically reducing NMDAR function in interneurons causes schizophrenia-like symptoms (Belforte et al, 2010). Interestingly, D-serine was found to improve positive, negative, and cognitive symptoms in patients with schizophrenia (Tsai et al, 1998(Tsai et al, , 1999. Collectively, this suggests that augmenting NMDA-mediated transmission through the NMDA coagonist binding site is promising for the pharmacotherapy of schizophrenia but perhaps also of epilepsy.…”
Section: D-serine and Novel Therapies In Epilepsymentioning
confidence: 98%
“…Changes in D-serine mediated cotransmission in epilepsy D-Serine is considered to be the predominant physiological ligand of the NMDAR coagonist site in forebrain regions (Panatier et al, 2006) and has been shown to be more effective in potentiating the NMDAR than glycine (Matsui et al, 1995;Stevens et al, 2010). Our data suggest that the coagonist binding sites of synaptic NMDARs in the hippocampus are not saturated, consistent with previous studies (Yang et al, 2003;Junjaud et al, 2006;Henneberger et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Most obvious is exogenous administration of agonists and partial agonists. Access of exogenous glycine to synapses utilising NMDARs is, however, limited by GlyT-1 and inhibition of this transporter is, therefore, more likely to be successful in increasing glycine levels at the NMDAR (Supplison and Bergman, 1997; Berger et al, 1998; Chen et al, 2003; Bergeron et al, 1998; Martina et al, 2004; Stevens et al, 2010). GlyT-1 inhibition has been shown to enhance LTP (Martina et al, 2004; Manahan-Vaughan et al, 2008) and cognition in both a social recognition test (Shimazaki et al, 2010) and an attentional set-shifting task (Nikifurik et al, 2011).…”
Section: Direct Modulationmentioning
confidence: 99%
“…Tonic NMDAR-mediated currents in interneurons are of similar magnitude when comparing hCSF with aCSF Another possible reason for underestimating tonic NMDARmediated currents in the slice preparation, as compared with in vivo, is related to the extracellular concentration of agonists for the NMDAR. The concentrations of glutamate, glycine and D-serine in the interstitial fluid and the CSF are in the low micromolar concentration (Herman & Jahr, 2007;Herman et al, 2011), and the ED 50 (EC 50 ) for these agonists is in the same concentration range, 3.5 (1.5) lM, 1.5-120 (0.54) lM and 3.3-3.5 lM, respec-tively (Laube et al, 1997;Chen et al, 2005;Daniels & Baldridge, 2010;Stevens et al, 2010). Superfusing slices with aCSF may decrease the effective concentration of these agonists.…”
Section: Tonic Nmdar Currents In Interneurons Are Inhibited By Low Comentioning
confidence: 99%